Antioxidant Content and Antioxidant Capacity of the Protein-Rich Powdered Beverages Enriched with Flax Seeds Gum - Justyna Bochnak-Niedźwiecka; Urszula Szymanowska; Ireneusz Kapusta; Michał Świeca (MDPI AG, 2022)
Powdered beverages produced from dried fruit and vegetables are new products whose properties may be tailored by adding efficient nutrients and functional ingredients. The analyses of low-molecular antioxidants and antioxidant properties as well as nutrient content and digestibility were tested in beverages enriched with lentil proteins (AGF) and flaxseed gum (FSG). A replacement of sprouted lentil flour with the AGF deteriorated the phenolic content. As a main source of phenolics and vitamin C, lyophilized parsley leaves and broccoli sprouts were recognized. (There was no clear effect of the FGS.) The highest content of phenolics was determined in the beverages with these additives without the AGS (c.a. 125 μg/g). The AGF significantly improved the ability to quench ABTS radicals and reduce power. The best results were for the beverages without the FSG. (The effect was enhanced by lyophilized fruit and green vegetables.) The lowest chelating power and ability to quench hydroxyl radicals were in the beverages based on the AGF (improvement by the FSG and green vegetables). The tailoring of beverages' recipes significantly increased protein content and did not affect nutrient digestibility. The modifications allow obtaining the beverages exhibiting multidirectional antioxidant properties, being a source of easily bioaccessible starch and proteins.